Studi Model Domenico-Robbins dan Ogata-Banks Terhadap Pola Persebaran Lindi di TPA Ngipik Kabupaten Gresik - Akmal, Abdillah; Munfarida , Ida; Auvaria , Shinfi Wazna; Negoro, Yusuf Tirto (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2022)
Leachate is a secondary product from piles of waste that decomposition of microorganism. Ngipik landfill is a landfill with an open dumping waste management system. This causes the soil and ground water to be suspected of being polluted due to landfill leachate. For this reason, it is necessary to identify the pattern of distribution and pollution of landfill leachate in order to determine how far the landfill leachate moves. This research uses the analytical solution method of Ogata-Banks and Domenico-Robbins to build a model for the distribution of contaminants in groundwater. The model was formed using MATLAB with COD and BOD parameters. The model data is validated with field data obtained from wells around the landfill. The results of measuring the quality of 3 wells are 29.8-31.8 0C, pH 5.7-6.4, DO 4.6-8 mg/L, COD 36.5-140.5 mg/L , and BOD 12.1-40.35 mg/L. The model simulation shows that COD and BOD are not detected at a distance of ± 278 m and ± 401 m. The validation results of the two models show that the Domenico-Robbins model has an error of 0.0016 for COD and 00.000467 for BOD, while Ogata-Banks has an error of 0.00287 for COD and 0.00417 for BOD.